Clinical efficacy of endoscopic dilation combined with bleomycin injection for benign anastomotic stricture after rectal surgery. Issue 33 (19th August 2022) - Miao, Xin; Liu, Li; Wang, Xiang; Fan, Zhining; Miao, Lin; Wang, Jiankun
Abstract : Benign anastomotic stricture is a frequent complication after rectal surgery. This study investigated the feasibility of endoscopic dilation combined with bleomycin injection for benign anastomotic stricture after rectal surgery. 31 patients who diagnosed with benign anastomotic stricture after rectal surgery were included in this study. 15 patients received simple endoscopic dilation (dilation group) and 16 patients received endoscopic dilation combined with bleomycin injection (bleomycin group). The clinical effect and adverse events were compared in the 2 groups. The strictures were managed successfully and the obstruction symptoms were relieved immediately. There were 2 minor complications in dilation group and 3 minor complications in bleomycin group. The difference was not significant between the 2 groups ( P > .05). During the follow-up, the mean reintervention interval was 4.97 ± 1.00 months in dilation group and 7.60 ± 1.36 months in bleomycin group. The median treatment times was 4 (range 3–5) in dilation group and 2 (range 2–3) in bleomycin group. The differences in the 2 groups were significant ( P < .05). Compared with endoscopic dilation, endoscopic dilation combined with bleomycin injection may reduce the treatment times and prolong the reintervention interval, which is a safe and effective endoscopic management for benign anastomotic stricture after rectal surgery.